PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SDN 37 CAKRANEGARA - Laela Hidayati Putri; Johan Mahyudi; Fitri Puji Astria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' critical thinking skills in Indonesian language lessons at SDN 37 Cakranegara's 4th grade have not developed optimally. Learning is still focused on textbooks, teachers have not assessed students' critical thinking abilities, and the learning model used by the teacher has not been able to improve students' critical thinking skills. This research aims to determine the effect of the Project Based Learning model on students' critical thinking skills and to understand the application of the Project Based Learning model in improving students' critical thinking skills. This study used an experimental method with a Nonequivalent Control Group Design. Data collection techniques included tests (pre-test and post-test), observation, and documentation. The results show that the Project Based Learning model influences students' critical thinking skills in Indonesian language lessons for 4th graders at SDN 37. The Project Based Learning model also improves students' critical thinking skills, as indicated by an increase in each critical thinking indicator, such as providing simple explanations, building basic skills, making inferences, providing further explanations, and setting strategies and techniques.